Performance consequences of automated workplace control - Dorner, Verena; Fellner-Röhling, Gerlinde (Frontiers in Behavioral Economics, 2025)
This study examines the impact of automated workplace control on employee performance and trust. In light of the rise in remote work and increasing use of algorithmic monitoring, we conduct a controlled experiment to investigate how workers' performance responds to control decisions made by an algorithm compared to a human. Moreover, we investigate spillovers on the subsequent trust in employers. Using a real-effort task and a trust game in an online experiment, we vary the source of control (human or algorithm) and control intensity (low, medium, high). Our findings reveal that control by a human principal (but not an algorithm) enhances worker performance, with no detrimental effects observed for higher control intensity. Despite the performance increase, being controlled by a human principal reduces trusting behavior on the extensive margin, i.e., the likelihood that agents entrust principals any positive amount of their endowment. Exploratory analyses suggest control by human principals is perceived more negatively than control by an algorithm. Our findings suggest that automated workplace control does not have negative ramifications for workers' performance, although it cannot generate the positive effects of human control either.